Ответы и объяснения

2014-02-14T18:23:34+00:00
2x+3/4(x-1)+3=1/4                                                                                                      2x+3/4x-3/4+3=1/4                                                                                                    2x+3/4x=3/4-3+1/4                                                                                                    2 3/4x=-2                                                                                                                  x=-2:11/4=-2*4/11=-8/11
2014-02-14T18:25:37+00:00
2x+3/4(x-1)+3=1/4
2x+3/4x-3/4+3=1/4
2x+0,75x=0.25+0.75-3
2.75x=-2
x=-2/2.75
x=-1/1.375=-8/11